2017
DOI: 10.1515/pielxxiw-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

The importance of physical examination in neurological nursing

Abstract: Introduction. An essential part of specialized nursing care is a physical examination. In neurological nursing, its aim is to identify the symptoms that result from damage to the nervous system. There is no literature on the use of physical examination in neurological nursing.Aim. The aim of this work is to present the significance of the use of physical examination in the work of a neurological nurse.Summary. Performing physical examination by nurses in neurological departments requires specialized knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Questions have been raised about the need for nursing students to learn such a broad range of physical assessment A significant proportion of nurses do not perform all elements of physical examinations, even though they are included in the training stage and should have such knowledge and skills. The reason for the incomplete use of physical examinations in Poland is due to many factors [19]. Our own research showed that the most common reason given for not performing a physical examination was that the workload was too heavy (59.6%).…”
Section: Discussionmentioning
confidence: 90%
“…Questions have been raised about the need for nursing students to learn such a broad range of physical assessment A significant proportion of nurses do not perform all elements of physical examinations, even though they are included in the training stage and should have such knowledge and skills. The reason for the incomplete use of physical examinations in Poland is due to many factors [19]. Our own research showed that the most common reason given for not performing a physical examination was that the workload was too heavy (59.6%).…”
Section: Discussionmentioning
confidence: 90%
“…Para tanto é necessário que ele possua clareza de sua função, autonomia, autoconfiança, conhecimento e habilidades, pois influenciaram na realização exame físico (Khoran, et al;. Em alguns estudos acerca da realização do exame físico em diferentes sistemas e populações, observa-se a importância de sua realização associada à habilidade e conhecimento do enfermeiro (Padykuła, et al, 2017;Martin, 2016;Borji, et al, 2018).…”
Section: Introductionunclassified